Effects of Dietary Supplementation With Bacillus subtilis, as an Alternative to Antibiotics, on Growth Performance, Serum Immunity, and Intestinal Health in Broiler Chickens - Qiu, Kai; Li, Cheng-liang; Wang, Jing; Qi, Guang-hai; Gao, Jun; Zhang, Hai-jun; Wu, Shu-geng (Frontiers in Nutrition, 2021)
Bacillus subtilis (B. subtilis) as in-feed probiotics is a potential alternative for antibiotic growth promoters (AGP) in poultry industry. The current study investigated the effects of B. subtilis on performance, immunity, gut microbiota and intestinal barrier function of broiler chickens. A 42-day feeding trial was conducted with a total of 600 one-day-old Arbor Acres broilers with similar initial body weight, which were randomly divided into 1 of 5 dietary treatments: the basal diet (Ctrl), Ctrl + virginiamycin (AGP), Ctrl + B. subtilis A (BSA), Ctrl + B. subtilis B (BSB), and Ctrl + B. subtilis A + B (1:1, BSAB). The results showed significantly increased average daily gain in a step-wise manner from the control, B. subtilis, to AGP groups. The mortality rate of the B. subtilis group was significantly lower than the AGP group. The concentrations of serum immunoglobulin G (IgG), IgA, and IgM in B. subtilis and AGP groups were higher than the control group, and B. subtilis groups had the highest content of serum lysozyme and relative weight of thymus. Dietary B. subtilis increased relative length of ileum and the relative weight of jejunum compared with the AGP group. The villus height (V), crypt depth (C), V/C, and intestinal wall thickness of jejunum in B. subtilis and AGP groups were increased relative to the control group. Dietary B. subtilis increased mRNA expression of ZO-1, Occludin, Claudin-1, as the same with AGP. The contents of lactic acid, succinic acid, and butyric acid in ileum and cecum were increased by dietary B. subtilis. Dietary B. subtilis significantly increased lactobacillus and bifidobacteria in ileum and cecum and decreased coliforms and Clostridium perfringens in cecum. Improved performance and decreased mortality rate observed in feeding trial could be accrued to positive effects of B. subtilis on immune response capacity, gut health, gut microflora balance and combination of two strains showed additional benefits on intestinal morphology and tight junction protein expressions. Therefore, it can be concluded that dietary B. subtilis A and B could be used as alternatives to synthetic antibiotics in promotion of gut health and productivity index in broiler production.